Zakon o minimalni plači - od sprejema do danes - Bobovnik, Andraž (Delavci in delodajalci, 2019)
The article summarizes the circumstances and the process of the adoption of the Minimum Wage Act (ZMinP) in 2010 and its changes in the years 2015 and 2018. It highlights the importance of social dialogue in the area of minimum wages and represents its efficiency and performance with a special emphasis on the period after 2010. The article seeks to answer the question as to why social dialogue in the field of minimum wage has not been successful in recent years and how to address the open issues in the area of minimum wage in the future.
Keywords: delodajalci; employers; minimalna plača; minimum wage; Minimum Wage Act; sindikati; social dialogue; socialni dialog; trade unions; Zakon o minimalni plači